2016
DOI: 10.1177/0042085916674057
|View full text |Cite
|
Sign up to set email alerts
|

Fostering the Cultural Experiences and School Engagement of Samoan American Students in Urban Schools

Abstract: We explored the associations of collective self-esteem and parent educational practices with school engagement in a sample of 128 Samoan middle and high school students in an urban school district. Simultaneous regression analysis revealed that each of these independent variables contributed to significant variance in school engagement. Specifically, the overall regression model accounted for 22% of the variance in school engagement. Collective self-esteem was the most significant association, followed by pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…Certainly, scholars have examined other individual and contextual factors that facilitate student engagement, beyond those that generate feelings of autonomy, belonging, and competence, including school size, school condition, disciplinary policies, classroom structure, task characteristics, school conditions, peer influence, curricular relevance, and student–teacher relationships (Borrero & Yeh, 2016 ; Greer et al, 2018 ). While this research has identified key practices and policies that can promote student engagement, such as giving students a choice in how to frame problems and tasks (Schmidt et al, 2018 ), it has largely side-stepped the question of whether and how student voice might matter either to engagement or to its psychological antecedents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Certainly, scholars have examined other individual and contextual factors that facilitate student engagement, beyond those that generate feelings of autonomy, belonging, and competence, including school size, school condition, disciplinary policies, classroom structure, task characteristics, school conditions, peer influence, curricular relevance, and student–teacher relationships (Borrero & Yeh, 2016 ; Greer et al, 2018 ). While this research has identified key practices and policies that can promote student engagement, such as giving students a choice in how to frame problems and tasks (Schmidt et al, 2018 ), it has largely side-stepped the question of whether and how student voice might matter either to engagement or to its psychological antecedents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An example of this has been research on students of migrant descent, with multi and intercultural identities considered an at-risk population regarding mental health, in which collective self-esteem shows direct effects on psychological, subjective, and socio-emotional well-being ( Crocker et al, 1994 ; Kim and Omizo, 2005 ; Du et al, 2017 ; Cornejo et al, 2020 ). Other studies have been conducted on racial minority students whose educational opportunities are affected by intergenerational background ( Thomas, 2017 ); others have focused on the interaction between family and school educational practices to show how collective self-esteem, as a cultural factor, promotes school engagement ( Borrero and Yeh, 2020 ). Studies have also been published that show the effect of collective self-esteem on the self-construals responsible for psychological well-being in students at the higher education level ( Yu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rather than assume a one-size fits all approach to "what works" in urban contexts, we focus on newcomer EBs, or recently-arrived students who learn new academic and linguistic content in a shortened period of time (Short & Boyson, 2012). We join other scholars in urban education (Borrero & Yeh, 2020;Kumi-Yeboah, 2020;Roxas, 2011;Volk, 2021) who seek to understand the educational experiences of distinct student populations, and ask:…”
mentioning
confidence: 99%